Kajian Dogmatis Tentang Baptisan Roh Kudus - Rajiman Andrianus Sirait (JURNAL LUXNOS, 2021)
Abstract: The understanding of the baptismal teachings of the Holy Spirit is so diverse. Every church has a different dogma. There are two Christian views, namely the existence of groups that are considered unbaptized by the Holy Spirit, and then there are more Christian elites who think they have been baptized with the Holy Spirit. In answering this, the author uses qualitative methods with a library study approach. The Holy Spirit can only be described by His position in the Trinity of God and all His works are Holy. The main function of dogma is to invite us to investigate ourselves and think critically. Simply put, we can understand that this dogma is a teaching in which it is in line with what is written in the Bible and that is seen and adapted in terms of context and time. The baptism of the Holy Spirit can also be defined as the work of the Spirit of God who unites believers with other believers in the Body of Christ. The sign of the baptism of the Holy Spirit does not always have to be marked by the gift of speaking in tongues alone. Abstrak: Pemahaman tentang ajaran baptisan Roh Kudus begitu beragam. Setiap gereja memiliki dogma yang berbeda. Ada dua pandangan Kristen, yaitu adanya kelompok yang dianggap belum dibaptis oleh Roh Kudus, kemudian lebih banyak lagi elit Kristen yang menganggap dirinya telah dibaptis dengan Roh Kudus. Dalam menjawab hal tersebut, penulis menggunakan metode kualitatif dengan pendekatan studi kepustakaan. Roh Kudus hanya dapat digambarkan dengan posisi-Nya dalam Trinitas Allah dan semua pekerjaan-Nya adalah Kudus. Fungsi utama dari dogma adalah mengajak kita untuk menyelidiki diri sendiri dan berpikir kritis. Sederhananya, Kita dapat memahami bahwa doktrin ini sejalan dengan doktrin yang tertulis di dalam Alkitab, dan dilihat serta disesuaikan dengan konteks dan waktu. Baptisan Roh Kudus juga dapat dipahami sebagai pekerjaan Roh Allah untuk menyatukan setiap pribadi yang percaya terhadap Kristus. Tanda-tanda baptisan Roh Kudus tidak selalu ditandai dengan karunia bahasa roh.